Rates of Forced Sexual Experiences Among High School Students From 2001 to 2019. Issue 21 (November 2022) - Marcantonio, Tiffany L.; Weese, James; Willis, Malachi
Public awareness of sexual assault and initiatives aimed at preventing sexual assault continue to increase over the years. However, whether rates of sexual assault have diminished because of such cultural shifts remains unclear. The purpose of this study was to assess if rates of sexual assault (i.e., forced sex) have changed over the past 18 years for adolescent girls and boys as well as potential differences across racial/ethnic identities. Using nationally representative data from the Youth Risk Behavioral Surveillance Survey from 2001 to 2019, we conducted logistic regressions to assess rates of experiences of forced sex by sex and by sex and racial/ethnic identity, while accounting for grade level. Participants included 135, 837 high school students. From 2001 to 2019, rates of forced sex maintained for girls; however, there was a decrease over time for boys. For girls, there were inconsistent differences in rates of forced sex by racial/ethnic identities. However, boys who identified as Black, Hispanic, Multi-Racial, and Other Race/Ethnicity were at higher risk to report forced sex than their White peers, until 2015; only Other Race/Ethnicity was at higher risk in 2019. As girls and boys aged, the risk of forced sex increased. Despite prevention efforts, rates of forced sex did not decrease from 2001 to 2019 for adolescent girls disregarding race/ethnicity, and for racial/ethnic minority boys. That rates of forced sex continue to be high is problematic as experiencing sexual assault at an earlier age is associated with myriad consequences. Further, results suggest current prevention initiatives may be inadequate at addressing risk factors for forced sex, and more broadly, sexual assault. Moving forward, researchers and educators may want to re-evaluate the strategies used to address and measure sexual assault experiences.